233k views
2 votes
Elio and Denise solved the equation, (-3n-8)(2n+4)=0. Their work is shown below.

Elio and Denise solved the equation, (-3n-8)(2n+4)=0. Their work is shown below.-example-1
User Dania
by
5.8k points

2 Answers

6 votes

Answer:

Elio is correct.

Explanation:

Only Elio is correct; he used the Zero Product Property correctly for both factors. For
-3n-8=0, he correctly got
n=-(8)/(3). For
2n+4=0, he remembered to subtract
4 from both sides to get
2n=-4, which yields
n=-2 as the other solution.

User Jlodenius
by
6.1k points
0 votes

Answer:

Elio's answer is correct.

Explanation:

Because a positive number becomes negative at the other side of the 'equal(=)' sign. Denise kept it positive which is wrong.

*2n+4=0 is to be seen.

User Rawnak Yazdani
by
6.3k points